EVALUASI PERATURAN DAERAH (PERDA) KABUPATEN TEGAL NOMOR 10 TAHUN 2006 TENTANG ALOKASI DANA DESA DI KECAMATAN ADIWERNA TAHUN ANGGARAN 2010 SAMPAI 2012 - Andri Pratama; Sulistyowati .; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2014)
ABSTRACTThis research is motivated from local regulation policy (Government) Tegal DistrictNo. 10 of 2006 on the allocation of village funds (ADD), especially in the planning process,use, accountability and ADD are held in the District Adiwerna. ADD implementationcommenced in 2007 after the promulgation of the previous year. However, theimplementation of the ADD in 2010 to 2012 cases of acts of corruption, accountability hasnot carried out and planning the use of which has not been fully focused on the TegalRegulation No. 10 2006. The purpose of this study is to describe and analyze the planningprocess, the use and accountability of ADD, the role of the community in theimplementation, and the reasons of failure of accountability ADD in the villages located inthe District Adiwerna.This study is a qualitative research, data collection techniques by means ofinterviews, documentation, as well as literature. Results of the study was to determine theplanning process, use, accountability and results from the presence of ADD which isdirected by the District government through the preparation of technical guidelines, the roleof rural communities in the implementation of ADD every year and know the reasons offailure of ADD in District Adiwerna liability due to human resources (HR ) villagegovernment is still low.Keywords: Evaluation, Policy, Rural Fund Allocation, Regional Regulation